Online counseling competences among Thai secondary school advisory teachers: a confirmatory factor analysis - Bovornpot Choompunuch; Dussadee Lebkhao; Wipanee Suk-Erb; Phamornpun Yurayat (Institute of Advanced Engineering and Science, 2026)
The increasing reliance on digital technology in education, accelerated by the COVID-19 pandemic, highlights the urgent need to understand online counseling competencies among secondary school advisory teachers. However, limited empirical evidence exists regarding the structure of these competencies in the Thai educational context. This study aimed to examine the components and validate a model of online counseling competences among secondary school advisory-teachers in Thailand. A total of 400 teachers from the Northeastern region were selected using multistage stratified random sampling. Data were collected through self-reported questionnaires and analyzed using second-order confirmatory factor analysis (CFA). The findings indicate that online counseling competences comprises three components: adaptive online counseling proficiency (AOC), school online counseling ethics (SCE), and secure comprehensive technology-integrated online counseling systems (SCS). The model demonstrated strong fit indices (χ2=76.240, df=70, p-value=0.284, χ2/df=1.089; root mean square error of approximation (RMSEA)=0.015; standardized root mean square residual (SRMR)=0.029; normed fit index (NFI)=0.990; comparative fit index (CFI)=1.000). This model provides a framework to guide training and policy development aimed at enhancing the effectiveness of online counseling services in Thai secondary schools.